Analisis Kinerja Keuangan Daerah Pemerintah Kota Bekasi Tahun Anggaran 2018 – 2022 - Dheandra Merza Hanifah; Ivan Yudianto (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research shows that the financial performance achievements of the Bekasi city government have not been maximized in realizing development for the welfare of the community. The method used is descriptive quantitative. Data collection techniques in this study include interviews, documentation, and literature studies. The results of the research show that the financial performance achievements of the Bekasi city government for the 2018 - 2022 fiscal year average DDF of 42.2% with a medium financial capacity category, average Regional Financial Independence of 77% with a delegation relationship pattern, average effectiveness of PAD is less effective with a ratio of 89.73%, an average operating expenditure of 80%, an average capital expenditure of 18%. Spending efficiency with an average of 84.75% in the efficient category. This shows that the average achievement is that the Bekasi City Government towards central government transfer funds is still more dominant than regional original income because the Bekasi City is still decentralized and most of the funds owned by the Bekasi City Government are prioritized for operating expenditures so that capital expenditures are relatively small and more to routine expenses or spending to fulfill activities. The Bekasi City Government has also focused on economic recovery during the COVID-19 pandemic, and overall performance achievements in Key Performance Indicators have been quite good.